2021
DOI: 10.1097/inf.0000000000003082
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in Children

Abstract: Background: Candida species are the most common cause of systemic fungal infections in children. Risk factors for candidemia vary in different patient populations, posing challenges for clinical prediction of infection. We describe the epidemiology and clinical disease of candidemia in children admitted to a tertiary pediatric hospital. Methods: Retrospective audit of children ≤18 years of age with candidemia at a tertiary pediatric hospital over a 16-year period. Results: There were 139 episodes of candidemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
2
16
4
Order By: Relevance
“…This study evaluated 342 candidemia episodes in 311 paediatric patients during a 13‐year period in a large university hospital in the Aegean region of Turkey. We found a higher rate of NAC (67.5%) candidemia than CA (32.5%) candidemia, similar to previous reports 8,22–27 . Based on the univariate analysis, a history of CoNS culture positivity in the last month, TPN and antifungal prophylaxis were significantly more common in the NAC group.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study evaluated 342 candidemia episodes in 311 paediatric patients during a 13‐year period in a large university hospital in the Aegean region of Turkey. We found a higher rate of NAC (67.5%) candidemia than CA (32.5%) candidemia, similar to previous reports 8,22–27 . Based on the univariate analysis, a history of CoNS culture positivity in the last month, TPN and antifungal prophylaxis were significantly more common in the NAC group.…”
Section: Discussionsupporting
confidence: 90%
“…1,26 NAC, particularly C. parapsilosis, shows an increasing prevalence in children with fungal bloodstream infections. [24][25][26][27] This rising trend of C. parapsilosis has been associated with many factors, such as biofilm formation resulting in an affinity for intravascular devices and prosthetic materials, colonisation of the gastrointestinal system and hand contamination by healthcare workers. use have been identified as risk factors for NAC candidemia in adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 However, a noticeable rise in candidaemia cases due to non-albicans Candida species particularly C. krusei and C. lusitaniae was recorded in paediatric patients of Australia and United States, respectively. 7,8 In contrast to the above findings, a recent multicentric study from India reported isolation of many rare yeasts from ICU-acquired candidaemia cases in paediatric ICUs at our centre. 9 The emergence of rare yeasts may be attributed to thermal adaptation, local climatic factors, aggressive medical intervention in critically ill patients, improvement in the identification of causative agent, and antifungal pressure.…”
contrasting
confidence: 67%